Pengaruh Sustainability Reporting Terhadap Kinerja Keuangan pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia (BEI) - Tsyaniah Tsyaniah; Mega Silvia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to evaluate the effect of sustainability reporting on financial performance in energy sector companies listed on the Indonesia Stock Exchange (IDX). Sustainability aspects are examined through three main dimensions, namely the economic, social and environmental dimensions. Financial performance is measured by the Return on Equity (ROE) indicator. A total of 64 companies were sampled using a purposive sampling approach for the period 2023. Data analysis was carried out using multiple linear regression methods. The analysis results show that the economic and social dimensions have a significant effect on ROE, while the environmental dimension does not show a significant effect. This study implies that strong sustainability disclosures, especially on economic and social aspects, can encourage the improvement of the company's financial performance.